Association of TIMP1 Levels and Liver Disease Progression Among HIV/HCV Co-infected, HIV Mono-, HCV Mono-infected, and Healthy Groups from the MASH Cohort (FS09-07-19). (24th October 2019) - Kim, Hyojung; Li, Tan; Hernandez, Jacqueline; Teeman, Colby; Tamargo, Javier; Sherman, Kenneth; Rouster, Susan; Abdel-Hameed, Enass; Jasmin, Juphshy; Seminario, Leslie; Liu, Qingyun; Zarini, Gustavo; et al.
Abstract: Objectives: Antiretroviral therapy has increased life expectancy for HIV infected patients; however, this population is developing chronic illnesses associated with aging. Liver disease is a major cause of non-AIDS mortality, characterized by progressive fibrosis. Infection with HIV and with Hepatitis C Virus (HCV) promotes liver fibrogenesis. Tissue inhibitor of metalloproteinase-1 (TIMP1), inhibits fibrosis regression and is profibrogenic. Association between TIMP1 and liver disease progression in an aging population of HIV/HCV co-infected, HIV mono-infected, HCV mono-infected, and healthy groups from the Miami Adult Studies on HIV (MASH) cohort in Miami, Florida, was investigated. Methods: Serum TIMP1 levels were determined by ELISA. A non-invasive estimate of liver fibrosis, FIB-4 score was calculated. Liver fibrosis was defined as FIB-4: Low <1.45, intermediate 1.45 < = FIB-4 < = 3.25, High >3.25. ANOVA with Tukey's test assessed the mean differences of FIB-4 score and TIMP1 level between groups, TIMP1 levels between 3 FIB-4 categories, and the effect of age on FIB-4 and TIMP1. Linear regression predicted the association of FIB-4 score and TIMP-1 level. Results: Mean age of the cohort was 54.3 ± 8.1 years with no difference between groups. Mean FIB-4 for HIV/HCV co-infected group was the highest among the 4 groups ( P  < 0.05). Mean TIMP1 for HIV/HCV co-infected group was also the highest among the 4 groups ( P  < 0.05). FIB-4 and TIMP1 were associated and remained so (β = 0.01, SE = 0.002, P  < 0.001) after adjusting for age. Mean TIMP1 for the high FIB-4 category was the highest among the 3 FIB-4 categories ( P  < 0.05). There was a direct effect of TIMP1 levels on FIB-4 category ( P  < 0.001). After adjusting for HIV/HCV co-infection ( P  < 0.001), HIV infection ( P  < 0.0001), HCV infection ( P  < 0.002), non-infection ( P  < 0.001) and age, the relationship between TIMP1 and FIB-4 remained significant. The adjusted TIMP1 mean for HIV/HCV co-infected group was significantly higher compared to HIV infected ( P  < 0.0001), HCV infected ( P  < 0.002), and healthy groups ( P  < 0.0001), regardless of age. Conclusions: Age is a significant factor of liver diseases progression. Our findings of the highest levels of TIMP1 in HIV/HCV co-infected group, which had the highest liver fibrosis regardless of age, supports the role of TIMP1 as a regulator in the progression of hepatic fibrosis. Funding Sources: National Institutes on Drug Abuse #5UO1DA040381.